Research on Communication Technology of OPGW Line in Distribution Network under Interference Environment - Li, Bo; Huang, Meiqin; Zhang, Huanyu; Lin, Mi; He, Shuyi; Chen, Liming (EAI Endorsed Transactions on Scalable Information Systems, 2023)
In optical fiber composite overhead ground wire (OPGW) networks, the current monitoring is mainly through installing electronic sensors on the cable and manually monitoring the video on the cable, where the interference plays an important role in the communication and monitoring based systems. In essence, the interference arises from aggressive frequency reuse, especially in the frequency-limited Internet of Things (IoT) networks. The existence of interference causes a negative effect on the system performance of communication systems and IoT networks including the OPGW networks. Hence, this article investigates the communication technology of OPGW line in distribution network under interference environment, where there is one primary link, one secondary link, and one legitimate monitor listening to the secondary link. The secondary user needs to transmit its message to the secondary receiver under the interference power constrained by the primary node. We firstly define the outage probability of legitimate monitoring based on the data rate, and then analyze the system performance by theoretically deriving a closed-form expression of the outage probability for the OPGW communication under interference environment. Simulation results are finally demonstrated to verify the correctness of the closed-form expression for the OPGW communication under interference environment, and show that the interference has a negative impact on the OPGW communication performance.
Keywords: Digital grid; data transmission; outage probability; analytical expression; OPGW communication